Pursuit game problem of an infinite system of differential equations with geometric and integral constraints - Waziri, Usman; Gafurjan, Ibragimov; Alias, Idham Arif; Ibrahim, Zarina Bibi (IOP Publishing, 2018)
The present paper considers a pursuit game problem of an infinite system of 1st-order differential equations in the space l 2. In the game, the player's control functions satisfy both geometric and integral constraints. The pursuer's action is to force the state of the system to coincides with another state for a finite time and the evader's action is to retrieve this. In each case, we obtain a condition for the completion of the game for which the pursuer's strategy is explicitly constructed. In addition, we study a control problem.